Karakteristik Belajar Siswa Gaya Belajar Siswa dan Pendekatan Individual dalam Pengajaran Rasulullah - Siti Aisyatunnadiya; Putri Talia; Fatimatuzzahra Fatimatuzzahra (AZKIA: Journal of Islamic Education in Asia, 2026)
In the modern era, the primary challenge in Islamic Education (PAI) is the stagnation of conventional teaching methods that utilize a "one size fits all" approach. This generalized strategy often ignores students' diverse cognitive and sensory profiles, resulting in suboptimal internalization of religious values and character development. Re-evaluating adaptive learning methods is crucial to ensuring pedagogical effectiveness amidst the diverse characteristics of contemporary learners. This study aims to analyze the integration of learning styles (visual, auditory, and kinesthetic) within the context of Islamic Education and to explore the relevance of the individualized approach exemplified by Prophet Muhammad PBUH as a solution to monotonous learning paradigms.This research employs a literature review method. Data were gathered through a systematic search of reputable databases, including Google Scholar, Scopus, and Web of Science (WoS). The literature reviewed spans the last ten years (2016–2026). Inclusion criteria consist of journal articles and books specifically addressing learning styles, Islamic educational psychology, and the Prophetic Sirah regarding the teaching methods of the Messenger. The key findings indicate that the classification of student learning styles significantly influences the speed of religious material absorption. The literature confirms that Prophet Muhammad PBUH consistently applied an individualized approach (tariqah fardiyyah) tailored to the intellectual capacity and psychological state of his companions. Synchronizing modern learning style identification with Prophetic methods is proven to create a more inclusive classroom environment and minimize the comprehension gap among students. The implementation of an individualized approach based on learning styles in Islamic Education not only enhances academic quality but also strengthens student character building. This study implies the importance of repositioning the role of educators as adaptive facilitators capable of collaborating contemporary psychological theories with Prophetic pedagogical values to create a more meaningful educational process.